2021
DOI: 10.1590/1807-1929/agriambi.v25n6p402-408
|View full text |Cite
|
Sign up to set email alerts
|

Morphophysiology of mini watermelon in hydroponic cultivation using reject brine and substrates

Abstract: HIGHLIGHTS Growth and leaf area of mini watermelon in hydroponic cultivation are reduced at electrical conductivity above 4.00 dS m-1. Electrical conductivity of up to 6.90 dS m-1 does not reduce the net photosynthesis of mini watermelon in hydroponic cultivation. Coconut fiber is the best hydroponic substrate for mini watermelon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Although salt stress caused some damage during the production phase of ‘Sugar Baby’ mini watermelon fruits and seeds, the seeds showed good viability and vigor. Both [ 24 ] and [ 25 ] showed that saline stress decreases ‘Sugar Baby’ mini watermelon growth, fruit production, and post-harvest quality. They showed that salt stress does not affect the mini watermelon photosynthetic rate due to its high photosystem II efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Although salt stress caused some damage during the production phase of ‘Sugar Baby’ mini watermelon fruits and seeds, the seeds showed good viability and vigor. Both [ 24 ] and [ 25 ] showed that saline stress decreases ‘Sugar Baby’ mini watermelon growth, fruit production, and post-harvest quality. They showed that salt stress does not affect the mini watermelon photosynthetic rate due to its high photosystem II efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The control treatment had the highest water consumption (54.2 L plant -1 ), while the 6.5 dS m -1 treatment had a water consumption of 42.7 L plant -1 . A reduction of water consumption with the increasing of nutrient solution salinity was expected and may be explained by the difficulty in absorbing water by the roots, due to the lower osmotic potential of the solution, with consequences on the development of the shoots and root system (Silva et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Salinity affects photosynthetic activity due to the accumulation of Na + and/or Clions in chloroplasts, which affect the biochemical and photochemical processes involved in photosynthesis. In addition, salt stress decreases CO 2 uptake because of salt stress, causing the closure of stomata, reducing the photosynthetic process (Silva et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…However, the tolerance of plants to salinity can vary according to cultivation system, among other factors. Hydroponic cultivation allows greater tolerance to salinity, because of the energy reorganization resulting from the minimization of the matric potential of system (Soares et al, 2020;Navarro et al, 2022) High concentrations of Na + (sodium) and Cl − (chloride) ions in the cell cytoplasm can inactivate enzymes as well as metabolites, reducing photosynthesis, stomatal conductance, transpiration, and internal carbon concentration, resulting in a decrease in the water-use efficiency (Souza et al, 2020;Silva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%